Synthesis and Study of the Structure-Activity Relationship of Antiproliferative N-Substituted Isosteviol-Based 1,3-Aminoalcohols - Dániel Ozsvár; Noémi Bózsity; István Zupkó; Zsolt Szakonyi (MDPI AG, 2024)
Starting from isosteviol, a series of diterpenoid 1,3-aminoalcohol derivatives were prepared via stereoselective transformations. The acid-catalysed hydrolysis and rearrangement of natural stevioside produced isosteviol, which was transformed into the key intermediate methyl ester. In the next step, an 1,3-aminoalcohol library was prepared by the reductive amination of the intermediate 3-hydroxyaldehyde obtained from isosteviol in a two-step synthesis. To study the effect of the carboxylate ester function at position 4, the free carboxylic acid, benzyl ester and acryloyl ester analogues were prepared as elongated derivatives in comparison with our earlier results in this field. The antiproliferative activity of compounds against human tumour cell lines (A2780, HeLa, MCF-7 and MDA-MB-231) was investigated. In our preliminary study, the 1,3-aminoalcohol function with N-benzyl or (1H-imidazol-1-yl)-propyl substitution and benzyl ester moiety seemed essential for the reliable antiproliferative activity. The results obtained could be a good starting point to further functionalisation towards more efficient antiproliferative diterpenes.